3D analysis of mitosis distribution highlights the longitudinal zonation and diarch symmetry in proliferation activity of the Arabidopsis thaliana root meristem. (20th October 2017) - Lavrekha, Viktoriya V.; Pasternak, Taras; Ivanov, Victor B.; Palme, Klaus; Mironova, Victoria V.
Summary: To date CYCB1;1 marker and cortex cell lengths have been conventionally used to determine the proliferation activity of the Arabidopsis root meristem. By creating a 3D map of mitosis distribution we showed that these markers overlooked that stele and endodermis save their potency to divide longer than the cortex and epidermis. Cessation of cell divisions is not a random process, so that mitotic activity within the endodermis and stele shows a diarch pattern. Mitotic activity of all root tissues peaked at the same distance from the quiescent center (QC); however, different tissues stopped dividing at different distances, with cells of the protophloem exiting the cell cycle first and the procambial cells being the last. The robust profile of mitotic activity in the root tip defines the longitudinal zonation in the meristem with the proliferation domain, where all cells are able to divide; and the transition domain, where the cell files cease to divide. 3D analysis of cytokinin deficient and cytokinin signaling mutants showed that their proliferation domain is similar to that of the wild type, but the transition domain is much longer. Our data suggest a strong inhibitory effect of cytokinin on anticlinal cell divisions in the stele. Significance Statement: 3D analysis of mitosis distribution in the Arabidopsis root meristem showed that there are two domains: in the proliferation domain all cells are able to divide; in the transition domain progressive cessation of cell divisions occurs within different cell files according to a diarch pattern. Protophloem ceases to divide the first, procambium the last, and the cortex cell starts to elongate in the middle.